Proposta de um método abrangente para o diagnóstico da medição de desempenho organizacional - Ferraz, Cláudia Augusto (2003)
In the last decades, most of the organizations has faced strong technical changes rather than managerial changes in terms of the performance evaluation. Such unbalance can mislead the achievement of all promised outputs of technical changes. Performance measurement could play an important role to reestablish the lost balance. Unfortunately, the traditional performance measurement systems, consistent with mass production systems, are inappropriate and the researchers and practitioners have been searching for new performance measurement frameworks. An extensive literature review has pointed out a lack of a comprehensive method to assess the performance measurement practices, i.e., there is a risk of changing the performance measurement practices with no information what the organization is really doing now. This dissertation aims to help to fill this gap developing a Comprehensive Performance Measurement Assessment Method. The method was developed from both a literature review and exploratory case study. It combines the existing methods from literature in a logical sequence in order to assess the performance measurement practices in three dimensions: individual performance measures, performance measurement system and the environment which it interacts.